When pride meets envy: Is social superiority portrayal in luxury advertising perceived as prestige or arrogance? - Sung, Billy; Phau, Ian (John Wiley & Sons, 2018)
This paper draws on the theoretical underpinnings of envy and pride in examining the effectiveness of social superiority portrayal in luxury advertising. Across two studies, benign (malicious) envy led consumers to perceive social superiority portrayal as an expression of authentic (hubristic) pride and, in turn, increased (reduced) luxury perception and positive brand attitude. These findings were replicated for both dispositional (Study 1 and 2) and state feeling of envy (Study 2), regardless of whether envy was self-reported or manipulated. These findings were found to be consistent in a comparison between luxury and premium brands. Taken together, this paper is the first to examine: (a) consumer responses toward social superiority portrayal in luxury advertising, (b) the interactive effect of envy and pride perceptions on luxury perception and brand attitude, and (c) the effectiveness of using social superiority portrayal as an advertising strategy for luxury and premium brands.